Applying the Contact Theory in Inclusive Education: A Systematic Review on the Impact of Contact and Information on the Social Participation of Students With Disabilities - Rademaker, Florianne; de Boer, Anke; Kupers, Elisa; Minnaert, Alexander (Frontiers in Education, 2020)
The social participation of students with disabilities in general education is lagging behind and negative peer attitudes are often mentioned as the main barrier. Contact Theory can serve as a rationale for interventions that aim to promote positive attitudes and thereby also the social participation of students with disabilities. This review aims to elucidate to what extent the intervention components contact and information are related to both the attitudes of typically developing peers and the social participation of students with disabilities. The results indicate that interventions combining contact and information are associated with more positive attitudes and one theme of social participation (i.e., interactions). It was, surprisingly, not possible to study the mediating role of peer attitudes as no studies addressed this. In sum, Contact Theory can be validated in primary inclusive education regarding typically developing students’ attitudes, but only partially regarding the social participation of students with disabilities.